Susceptibility-Weighted Magnetic Resonance Imaging in the Evaluation of Dementia - Larsen, James P. (Radiol Case Rep, 2015)
An 88-year-old woman with a clinical diagnosis of Alzheimer's disease and advanced dementia, was evaluated with standard MRI of the brain as well as Susceptibility Weighted Imaging (SWI) with the MRI. SWI revealed more extensive brain microhemorrhages than standard MRI techniques, allowing the radiologic diagnosis of cerebral amyloid angiopathy. SWI shows promise as a more sensitive diagnostic tool than standard brain MRI for the evaluation of patients with dementia.